Exploring the relationship between informal learning activities and learning motivations among college students - Shi, Yuewei (American Journal of Education and Learning, 2025)
Informal learning is a significant and widespread form of education among college students, occurring in various flexible learning environments. It encompasses different activities initiated by diverse motivational factors. This study aims to explore the relationship between informal learning activities and motivational factors among college students. A survey research method was employed, utilizing Lohman’s Informal Learning Activities Survey and the Work Preference Inventory as instruments. The study involved 160 college students. Data analysis included independent t-tests, stepwise regression, and Pearson-product correlations. Results indicated that adult learners exhibit higher levels of informal learning activities compared to traditional college students. Additionally, students with higher intrinsic motivation tend to engage more in informal learning. Motivation related to challenges was also positively associated with informal learning activities. The findings suggest that college educators and practitioners should establish a variety of accessible learning resources both inside and outside the classroom to motivate students to participate in informal learning. Furthermore, understanding the psychological needs of adult and traditional students can aid educators in designing challenging discussions and assignments, thereby fostering greater engagement in informal learning activities.